(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
In this paper ultrasound was applied in Savinase shrink-proof finishing process for wool fabric. A two-step procedure was adopted. Initially, hydrogen peroxide was used for pre-treatment in order to facilitate the subsequent enzymatic attack and to peel the outer scale layer effectively. The effects of enzyme concentration, temperature, time and ultrasonic power were explored through orthogonal experiments thoroughly. The results showed that ultrasound could remarkably speed up the scale-peeling process and greatly improve the shrinkage of wool fabrics. In contrast with the results obtained under conditions without the presence of ultrasound, much better shrinkages were obtained under ultrasound. Moreover, the weight loss and strength reduction were within acceptable limits. Therefore, ultrasound became a beneficial means for wool anti-felting treatment in enzymatic process. It helped to achieve better results in lesser time and lower temperature. The optimal technology was Savinase concentration (owf) 0.8%, temperature 50 °C, pH=8.5, time 40 min, ultrasonic power 175 W and bath ratio 25:1. Under these conditions, the shrinkage, weight loss and tensile strength of treated sample were 1.1%, 5.40% and 417N respectively.